Strategi Pemasaran Inklusif untuk Meningkatkan Partisipasi Dana Pensiun Pekerja Sektor Informal di Indonesia: Analisis Hambatan, Segmentasi Pasar, dan Rekomendasi Implementasi - Syarifudin Yunus; Farid Nabil Elsyarif (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study on inclusive marketing strategies to increase participation in pension funds among informal sector workers in Indonesia was conducted using a descriptive method with a mixed-methods approach, with a sample of 100 informal workers in the Greater Jakarta area. The study concluded that barriers to pension fund/DPLK participation among informal sector workers include: the perception that pension funds are illiquid (difficult to withdraw) at 28%, lack of education at 22%, the fact that participation is not mandatory or a lack of awareness at 19%, the lack of digital access at 13%, the perception that the system is absurd at 13%, and the perception that it is only for office workers at 5%. A transformation of the pension fund/DPLK marketing strategy is needed, shifting from a product-oriented approach to a participant-centered one. Segmentation of informal workers to increase pension fund participation can be divided into 1) traditional informal groups (lower tier), such as day laborers, street vendors, domestic workers, small-scale merchants, and micro-scale ride-hailing drivers; and 2) modern informal groups (upper tier), such as contractors, content creators, artists, consultants, and gig economy workers with medium to large-scale economic activities. Concrete recommendations to increase DPLK participation among informal workers involve shifting the DPLK approach from a conventional model to an inclusive-digital model, with a focus on 1) prioritizing community-based financial literacy, 2) flexibility, and 3) inclusivity through pension digitization.